Migration routes and conservation status of the Whooper Swan Cygnus cygnus in East Asia - Ao, Peiru; Wang, Xin; Meng, Fanjuan; Batbayar, Nyambayar; Moriguchi, Sachiko; Shimada, Tetsuo; Koyama, Kazuo; Park, Jinyoung; Kim, Hwajung; Ma, Ming; et al. (Wildfowl, 2020)
The migration routes and migratory patterns of Whooper Swans Cygnus cygnus summering in western Mongolia have not previously been described and the status of East Asian population is currently uncertain. Here we therefore use a combination of satellite tracking data, sightings of colour-marked individuals, published literature and expert knowledge to determine their distribution and site-use more precisely. Results indicated that the swans’ summer distribution extended further than had previously been recorded, with three new wintering areas (in Xinjiang, Qinghai, Gansu and Beijing) identified for the species in China. The East Asian Whooper Swan population was estimated to number 57,690 individuals, generating a new 1% threshold of 577 birds for determining sites of international importance for the species in the region. Using count data from winters 2011/12–2018/19, we identified eight wintering sites of international importance for the species in China, six in South Korea and 14 in Japan. Annual variation in national count totals highlighted the need to improve survey effort in China. Individual swans showed considerable within-winter fidelity to their wintering sites, with limited exchange between wintering areas. Migration duration, stopover duration, the number of stopover sites and migration legs were significantly greater in spring than in autumn, whilst migration speed was slower in spring than in autumn. Assessment of the habitats frequented found seasonal variation in the proportion of time that the swans spent on arable crops, pasture, wetlands and open water. From their GPS locations, 46.9%, 25.5%, 35.3% and 0.0% of the tagged swans were in protected areas during the summer, autumn staging, winter and spring staging periods, respectively. Our results provide a basis for the conservation of Whooper Swans in East Asia and illustrate the need for improved monitoring and further research into their migration, particularly for informing the protection and management of the main stopover and wintering sites for the species in China.